ENHANCEMENT OF WATER PRODUCTION USING SOLAR STILLS COUPLED WITH LOW POWER PV/DC HEATER - Amran, Noranaty Athirah (Universiti Teknologi PETRONAS, 2017)
Water shortage and contamination circumstance are spreading fast in all kinds of different backgrounds particularly in the developing nations. Among the accessible filtration advancements, Distillation process by using solar power turns out to be an appropriate answer for settling this current issue. This sustainable power source innovation works on a fundamental rule of which the sun based radiation enters through the glass surface inside a closed chamber touching the black surface bringing about evaporation and condensation process, which is trapped inside. Be that as it may, the refined water created by the solar still is limited. Henceforth, this paper introduces the exploratory consequences of the execution of the solar still utilizing the combination of PV/DC heater. This trial will be led in Universiti Teknologi Petronas (UTP) solar field testing lab. Theoretically, the more power heat energy supply, the higher rate of water production.